2006
DOI: 10.1038/sj.npp.1301133
|View full text |Cite
|
Sign up to set email alerts
|

The Selective mGlu5 Receptor Antagonist MTEP, Similar to NMDA Receptor Antagonists, Induces Social Isolation in Rats

Abstract: It has repeatedly been shown that uncompetitive N-methyl-D-aspartate (NMDA) receptor antagonists can mimic certain aspects of positive and negative symptoms of schizophrenia in human volunteers and laboratory animals. The purpose of the present study was to expand these findings and to determine whether the selective metabotropic glutamate receptor subtype 5 (mGluR5) antagonist, MTEP (3-[(2-methyl-1,3-thiazol-4-yl)ethynyl]pyridine), could induce similar effects in Wistar rats. First, MTEP (1.0-10.0 mg/kg; intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 77 publications
(86 reference statements)
7
47
1
6
Order By: Relevance
“…Thus, improving effects of CFMTI on NMDA antagonist-induced behavioral alterations are compatible with our working hypothesis, expanding the use of CFMTI to dopaminergic-independent neuronal control of psychiatric behavior. In support of this idea, an mGluR5 antagonist was reported to impair social interaction in rats (Koros et al, 2007). Melendez et al (2005) reported that DHPG administered by reverse microdialysis into mPFC elicited glutamate release that was blocked by coapplication of (R,S)-1-aminoindan-1,5-dicarboxylic acid and LY367385 with DHPG, suggesting that mGluR1 in mPFC may play a role in regulating glutamate release.…”
Section: F B Cmentioning
confidence: 83%
“…Thus, improving effects of CFMTI on NMDA antagonist-induced behavioral alterations are compatible with our working hypothesis, expanding the use of CFMTI to dopaminergic-independent neuronal control of psychiatric behavior. In support of this idea, an mGluR5 antagonist was reported to impair social interaction in rats (Koros et al, 2007). Melendez et al (2005) reported that DHPG administered by reverse microdialysis into mPFC elicited glutamate release that was blocked by coapplication of (R,S)-1-aminoindan-1,5-dicarboxylic acid and LY367385 with DHPG, suggesting that mGluR1 in mPFC may play a role in regulating glutamate release.…”
Section: F B Cmentioning
confidence: 83%
“…MPEP has been shown to potentiate NMDA receptor antagonist deficits in learning and memory (Homayoun et al, 2004;Campbell et al, 2004), while high doses of MPEP alone will impair DMTP and water maze performance (Ballard et al, 2005). The related mGlu 5 receptor antagonist MTEP has also been shown to induce social isolation in rats (Koros et al, 2007). On the other hand, mGlu 5 PAMs have been shown to have some positive effects on cognition.…”
Section: Treatmentmentioning
confidence: 98%
“…Defense behaviors relevant to depression were evaluated in a forced swimming test, scoring the total duration of immobility and swimming during a 5-min test session in glass cylinders containing water, as previously described [14]. Social interaction was evaluated as previously described [19,20] by measuring the amount of time spent by each rat in a pair sniffing, grooming, following, kicking, mounting, jumping on, wrestling/boxing, and crawling under/over the partner during a 10-min period of interaction. Anxiety-like behavior was evaluated using an elevated plus-maze by measuring during 5 [14].…”
Section: Assessment Of Emotional Parametersmentioning
confidence: 99%